Profitability or industrial relations: What explains manufacturing performance across Indian states? - Anirban Karak; Deepankar Basu (University of Massachusetts, Department of Economics, 2017)
We use a state-level panel data set for the period 1969-2005 to analyze the relative importance of profitability (rate of profit) and industrial disputes (man-days lost to all industrial disputes per worker) in explaining cross-state variations of manufacturing sector performance in India. Using three different measures of manufacturing performance - net value added, investment and employment - we find that profitability is more significant than industrial disputes in explaining the variation of manufacturing sector performance across Indian states.
Keywords: B50; C26; O10; 330; manufacturing performance; profitability; industrial disputes